The Effect of the grant of a Boiled Egg to Increased Levels of Hemoglobin (Hb) in Pregnant Women with Anemic at Cerme Village Health Center Kediri Regency in 2022 - Khofidhotur Rofiah; Betanuari Sabda Nirwana; Ira Damayanti; Kusni Sri Mawarti (Journal for Quality in Public Health, 2022)
Anemia is a condition of decreased red blood cells or hemoglobin, thus decreasing the capacity of haulage needs oxygen to organs in the mother and fetus are diminished. The results of a preliinary survey conducted in gretting pregnant as much as 99 of pregnant women are anemic as many as 36 pregnant women, and 63 pregnant women not anemic.The purpose of the research is to analyze the effect of the grant of a boiled egg to increased levels of hemoglobin (Hb) in pregnant women with anemic in Poskesdes Cerme Kediri Regency year 2022.This type of reseach is one approach to experimental quasy group pre test-post test design. The population in this research as much as 15 pregnant women with anemic, whereas the sample in this research is the entire amount of the existing population of pregnant women with anemic by using total sampling. Analysis of research test t-test and independent sample t-test.Research results showed the t-test in the get before and after given a boiled egg that is the p value of 0,000 or p < a (0,05). On independent test sample t-test in the get value of 0,001 p  or p < a (0,05), which means there’s influence after consuming boiled eggs to increased levels of hemoglobin.From the results of the study prove that consumption of boiled egg everyday can help improve hemoglobin levels in pregnant women with anemic, so it is recommended for pregnant women with anemic to consume boiled egg a day 1 rounds in the morning to raise the levels of hemoglobin.